2022
DOI: 10.3390/ani12131718
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Insights into the Gene Network of cis9, trans11-Conjugated Linoleic Acid Biosynthesis in Bovine Mammary Gland Epithelial Cells

Abstract: The objective of the study was to elucidate the stearoyl-coenzyme A desaturase (SCD1)-dependent gene network of c9, t11-CLA biosynthesis in MAC-T cells from an energy metabolism perspective. The cells were divided into the CAY group (firstly incubated with CAY10566, a chemical inhibitor of SCD1, then incubated with trans-11-octadecenoic acid, (TVA)), the TVA group (only TVA), and the control group (without CAY, TVA). The c9, t11-CLA, and TVA contents were determined by gas chromatography. The mRNA levels of SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
0
0
Order By: Relevance
“…Specifically, trans-10, cis-12 CLA inhibits the expression of SCAP and INSIG1, which are responsible for the abundance of nuclear SREBP1 (nSREBP1), thereby suppressing the activation of SREBP1. Subsequently, mRNA levels of SREBP1 downstream genes ACACA, FASN, and SCD1 are all downregulated [66,67]. In vitro studies have shown that trans-10, cis-12 CLA treatment does not alter the transcription and translation levels of nSREBP1, but directly suppresses and reduces its mRNA levels when 26S protease activity is inhibited.…”
Section: Regulation Of Triglyceride Synthesis By Trans-10 Cis-12 Clamentioning
confidence: 99%
“…Specifically, trans-10, cis-12 CLA inhibits the expression of SCAP and INSIG1, which are responsible for the abundance of nuclear SREBP1 (nSREBP1), thereby suppressing the activation of SREBP1. Subsequently, mRNA levels of SREBP1 downstream genes ACACA, FASN, and SCD1 are all downregulated [66,67]. In vitro studies have shown that trans-10, cis-12 CLA treatment does not alter the transcription and translation levels of nSREBP1, but directly suppresses and reduces its mRNA levels when 26S protease activity is inhibited.…”
Section: Regulation Of Triglyceride Synthesis By Trans-10 Cis-12 Clamentioning
confidence: 99%